MELIHAT DAN MERASAKAN TAMPILAN GRAFIS LAYAR TELEPON SELULAR - Karnita, Rosa (FSRD ITENAS, 2011)
Abstract Nowadays the mobile-phoneÂ is an indispensable tool in daily activities. Mobile-phone screen as one of many factors of discussion in a level user interface, the main focus in this study given the display screen as the spearhead of communication between the phone and its users. When a display screen is not able to achieve satisfactory results for its users, it needs to be revisited how to design a graphical display on the screen. The problem is formulated surrounds how much the display phone can influence the user's convenience. How does the concept in order to function and function aesthetics applied to display the phone screen? What is the role of visual communication in designing the layout and communication for the phone user? In addition, the development of Creative Industries in Indonesia are increasing rapidly today should be followed by the ability of creative human resources, so can produce competitive products that can captivate even the national market can penetrate the international market. This topic was raised with the aim of generating concept in order to well-designed as an aesthetic function to a better cell phone screen interface design, through a variety of disciplines related cooperation so as to applied by the local manufacturing industry to compete in their own country. Research methods used include questionnaires and analysis of several case studies phones using visual communications design standpoint. By pulling common thread between the theoretical review and case study, it found that the display mobile-phone screen as a whole (integration between letters, colors, icons, layout, proportion and composition) has been influencing the user's convenience, both directly and indirectly. Aesthetics function and uses function are relatedÂ with one of the user interface principles which is consistent with the principles of visual communication design. Keywords: mobile-phone screen, creative industries, aesthetics, Visual Communication Design Â Abstrak Dewasa ini telepon selular (ponsel) merupakan alat yang mutlak diperlukan dalam kegiatan sehari-hari. Layar ponsel sebagai salah satu faktor dari sekian bahasan dalam tataran user interface, menjadi sorotan utama dalam kajian ini mengingat tampilan layar sebagai ujung tombak komunikasi antara ponsel dengan penggunanya. Ketika suatu tampilan layar tidak mampu mewujudkan hasil yang memuaskan bagi penggunanya, perlu ditinjau kembali bagaimana merancang suatu tampilan grafis pada layar ponsel. Permasalahan yang dirumuskan melingkupi seberapa besar pengaruh tampilan layar ponsel terhadap kenyamanan pengguna? Bagaimana konsep fungsi guna dan fungsi estetika diaplikasikan untuk tampilan layar ponsel?Bagaimana peran Desain Komunikasi Visual (DKV) dalam perancangan tata letak dan komunikasi antara ponsel dengan pengguna? Selain itu, perkembangan Industri Kreatif di Indonesia yang meningkat pesat saat ini seyogyanya diikuti oleh kemampuan sumber daya manusia yang kreatif, sehingga dapat menghasilkan produk kompetitif yang dapat menarik hati pasar nasional bahkan dapat menembus pasar internasional. Topik ini diangkat dengan tujuan menghasilkan konsep fungsi guna maupun fungsi estetik untuk suatu rancangan interface layar ponsel yang lebih baik, melalui kerjasama berbagai disiplin ilmu terkait sehingga dapat diaplikasikan oleh industri manufaktur lokal agar dapat bersaing di negara sendiri. Metode penelitian yang digunakan meliputi kuesioner dan analisis studi kasus beberapa ponsel menggunakan sudut pandang perancangan Komunikasi Visual. Dengan menarik benang merah antara tinjauan teoritis dan hasil studi kasus, ditemukan bahwa tampilan layar ponsel secara keseluruhan (integrasi antara huruf, warna, ikon, tata letak, proporsi dan komposisi) sangat mempengaruhi kenyamanan pengguna baik secara langsung maupun tidak langsung. Fungsi guna dan fungsi estetika terkait dengan salah satu prinsip user interface yang selaras dengan prinsip-prinsip perancangan komunikasi visual. Kata kunci: layar ponsel, industri kreatif, estetika, DKV